1998
DOI: 10.1016/s0006-3495(98)77975-5
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Polystyrene Microbeads Using Dielectrophoretic/Gravitational Field-Flow-Fractionation

Abstract: The characterization of a dielectrophoretic/gravitational field-flow-fractionation (DEP/G-FFF) system using model polystyrene (PS) microbeads is presented. Separations of PS beads of different surface functionalization (COOH and none) and different sizes (6, 10, and 15 microm in diameter) are demonstrated. To investigate the factors influencing separation performance, particle elution times were determined as a function of particle suspension conductivity, fluid flow rate, and applied field frequency and volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 48 publications
1
168
0
Order By: Relevance
“…In this paper, we studied the effects of such exposure under the conditions most appropriate to DEP manipulations of cells, especially to cell DEP/FFF (field-flow fractionation) [45,46] sorting and DEP trapping [22,23,25]. Our experiments showed that under these conditions cell membrane integrity as revealed by trypan blue dye exclusion test was not compromised, and that cells were not stopped from proliferation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this paper, we studied the effects of such exposure under the conditions most appropriate to DEP manipulations of cells, especially to cell DEP/FFF (field-flow fractionation) [45,46] sorting and DEP trapping [22,23,25]. Our experiments showed that under these conditions cell membrane integrity as revealed by trypan blue dye exclusion test was not compromised, and that cells were not stopped from proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Inside a nonuniform standing field like that used in our experiments, the overall field stress also results in a nonzero dielectrophoretic force given by (4) where p(f) is the polarization factor, namely, the ratio of the voltage dropped across the bulk solution to that applied to the electrodes. This dielectrophoretic force can be made suffciently strong to overcome the sedimentation force and cause cell levitation in the sub-MHz frequency range where Re(f CM ) is negative, an effect that is exploited in cell sorters based on DEP/FFF [45,46]. Fig.…”
Section: Ac Field Induced Membrane Potential Did Not Cause the Observmentioning
confidence: 99%
“…Combining Equations 1 and 4, we find that a repulsive DEP force and the sedimentation force will balance when the height of the cell above the electrode plane is given by 10,19,27 h eq = 2πd log…”
Section: Theorymentioning
confidence: 99%
“…Besides, several complex components such as a high numerical aperture lens and extremely precise motion translation stages are required, which may further inhibit the practical application of optical tweezers due to higher system cost. Dielectrophoresis (DEP) is another widely used technology that has been exploited in the past decade to separate polystyrene beads [12], and multiwall CNTs based sensors [13]. This technology provides a parallel and rapid method for micro-/nano-manipulation.…”
Section: Introductionmentioning
confidence: 99%